piggyPrime: High-Efficacy Prime Editing in Human Cells Using piggyBac-Based DNA Transposition - Wolff, Jonas Holst; Haldrup, Jakob; Thomsen, Emil Aagaard; Andersen, Sofie; Mikkelsen, Jacob Giehm (Frontiers in Genome Editing, 2021)
Prime editing is a novel genome editing technology that allows a wide range of tailored genomic alterations. Prime editing does not involve homologous recombination, but suffers from low efficacy. Here, we demonstrate piggyPrime, a transfected single-vector system based on piggyBac DNA transposition for genomic integration of all prime editing components in human cells allowing easy and effective transgenesis with prime editing efficacies up to 100% in cell lines.